Solar Ultraviolet Irradiance Observations of the Solar Flares During the Intense September 2017 Storm Period. Issue 10 (2nd October 2018) - Chamberlin, P. C.; Woods, T. N.; Didkovsky, L.; Eparvier, F. G.; Jones, A. R.; Machol, J. L.; Mason, J. P.; Snow, M.; Thiemann, E. M. B.; Viereck, R. A.; Woodraska, D. L.
Abstract: A large outburst of flares occurred between 4–10 September 2017 when new magnetic flux emerged into and strengthened an existing active region, National Oceanic and Atmospheric Administration Region 12673. This intense solar storm period included X9.3 (6 September) and X8.2 (10 September) flares, the largest flares that have occurred during Solar Cycle 24, as well as 39 M‐class flares and three additional X‐class flares. Another X‐class flare from this active region was observed on the farside of the Sun from Mars Atmosphere and Volatile EvolutioN prior to the September events, along with other large M‐class flares, showing the potential for how farside irradiance monitoring can improve flare prediction at Earth for 1‐ to 13‐day forecasts. This September 2017 flare period is similar to other famous storm periods such as the 18 October to 5 November 2003 Halloween storm that produced 14 X‐class flares and 137 M‐class flares and the 6–10 September 2005 period that had 11 X‐class and 68 M‐class flares. All of these storm periods occurred in the declining phase of the solar cycle when solar activity had decreased significantly from solar maximum levels. This paper focuses on a number of solar irradiance observations at ultraviolet (0–190 nm) wavelengths during the September 2017 storm period and the advantages that an ensemble of measurements and models have for studying solar flares. Key Points: The largest outburst, in frequency and magnitude, of Solar Cycle 24 occurred late in the cycle from 4 to 10 September 2017 These solar flares were well observed in the EUV by SDO EVE and other solar EUV irradiance instruments and modeled by FISM The 6 and 10 September X‐class flares are remarkably similar in physical evolution and irradiance spectral evolution